PERSEPSI SISWA KELAS XI KULINER SMK TIGAMA PEKANBARU TERHADAP APLIKASI OBENKYO SEBAGAI MEDIA PEMBELAJARAN HIRAGANA - Tusofia, Witasha Afina; Basri, Merri Silvia; Nimashita, Hana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: This study analyzes students' perceptions of using the Obenkyoapplication as a learning medium for Hiragana. This application was chosen because ofits interactive features, such as writing exercises, character recognition, and evaluationtests. This research employed a descriptive quantitative method with 32 students ofClass XI Culinary at SMK Tigama Pekanbaru as respondents. Data were collectedthrough a Likert-based questionnaire and analyzed descriptively. The results showedthat students responded positively to the application, with the highest average score onthe flexibility of time and location indicator (3.50). This study concludes that theObenkyo application is effective as a learning medium for Hiragana, despite limitationsin device accessibility and application language guides.Key Words: Students' perception, learning media, Obenkyo application, Hiragana